Bovine Milk Extracellular Vesicles (EVs) Modification Elicits Skeletal Muscle Growth in Rats - Parry, Hailey A.; Mobley, C. Brooks; Mumford, Petey W.; Romero, Matthew A.; Haun, Cody T.; Zhang, Yufeng; Roberson, Paul A.; Zempleni, Janos; Ferrando, Arny A.; Vechetti, Ivan J.; McCarthy, John J.; Young, Kaelin C.; et al. (Frontiers in Physiology, 2019)
The current study investigated how bovine milk exosomes affected rotarod performance and biomarkers of skeletal muscle physiology in young, growing rats. Twenty-eight-day Fisher 344 rats were provided an AIN-93G-based diet for four weeks that either remained unadulterated (exosome and RNA-sufficient (ERS; n=12)) or was sonicated (exosome and RNA-depleted (ERD; n=12)). Prior to (PRE) and on the last day of the intervention (POST), animals were tested for maximal rotarod performance. Following the feeding period, the gastrocnemius muscle was analyzed at the histological, biochemical, and molecular levels and was also used to measure mitochondrial function and reactive oxygen species (ROS) emission. A main effect of time was observed for rotarod time (PRE>POST, p=0.001). Terminal gastrocnemius mass was unaffected by diet, although gastrocnemius muscle fiber cross sectional area was 11% greater (p=0.018) and total RNA (a surrogate of ribosome density) was 24% greater (p=0.001) in ERD. Transcriptomic analysis of the gastrocnemius indicated that 22 mRNAs were significantly greater in ERS versus ERD (p<0.01), whereas 55 mRNAs were greater in ERD versus ERS (p<0.01). There were no differences in gastrocnemius citrate synthase activity or mitochondrial coupling (respiratory control ratio), although mitochondrial ROS production was lower in ERD gastrocnemius (p=0.016), which may be explained by an increase in glutathione peroxidase protein levels (p=0.020) in ERD gastrocnemius. Dietary exosome profiling confirmed that sonication in the ERD diet reduced exosome content by ~60%. Our findings demonstrate that bovine milk exosome depletion through sonication elicits anabolic and transcriptomic effects in the gastrocnemius muscle of rapidly maturing rats. While this did not translate into a functional outcome between diets (i.e., rotarod performance), longer feeding periods may be needed to observe such functional effects.